2014
DOI: 10.1103/physreva.90.023611
|View full text |Cite
|
Sign up to set email alerts
|

Heating from continuous number density measurements in optical lattices

Abstract: We explore the effects of continuous number density measurement on atoms in an optical lattice. By integrating a master equation for quantum observables, we calculate how single particle correlations decay. We consider weakly-and strongly-interacting bosons and noninteracting fermions. Even in the Mott regime, such measurements destroy correlations and increase the average energy, as long as some hopping is allowed. We explore the role of spatial resolution, and find that the heating rate is proportional to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We also note that our model is different from a dissipative model described by a master equation, where one expects that the dissipative process eventually destroys subtle correlations underlying the quantum critical behavior, thereby leading to a high-temperature mixed steady state. Indeed, recent works have suggested that such steady states exhibit static properties similar to classical thermal equilibrium systems [47][48][49] and infinite-temperature states [50,51]. In contrast, we show that continuous observation can sustain the quantum critical behavior and gives rise to unique phenomena due to the measurement backaction.…”
Section: Effective Non-hermitian Hamiltoniansmentioning
confidence: 58%
“…We also note that our model is different from a dissipative model described by a master equation, where one expects that the dissipative process eventually destroys subtle correlations underlying the quantum critical behavior, thereby leading to a high-temperature mixed steady state. Indeed, recent works have suggested that such steady states exhibit static properties similar to classical thermal equilibrium systems [47][48][49] and infinite-temperature states [50,51]. In contrast, we show that continuous observation can sustain the quantum critical behavior and gives rise to unique phenomena due to the measurement backaction.…”
Section: Effective Non-hermitian Hamiltoniansmentioning
confidence: 58%
“…However, in general, the act of position measurement causes the atom's energy to increase linearly with time [30]. In our scheme, this increase in energy is mitigated by the simultaneous use of sideband cooling at a rate Γ RSC .…”
mentioning
confidence: 97%
“…Due to the difficulty of generalizing the original derivations [43][44][45][46][47], a continuous position measurement model for indistinguishable particles has long remained elusive [37] because photons scattered at two different sites can be distinguished. The measurement indistinguishability could not play a nontrivial role for the cases of site-resolved measurement [38][39][40][41][42] and single particle models [43][44][45][46][47]. Note that we do not assume that the degrees of freedom of relative positions are frozen unlike in a rigid system [54,58,59].…”
Section: B Time-evolution Equation For Indistinguishable Particlesmentioning
confidence: 99%
“…We demonstrate these results by numerical simulations of correlated quantum walks. In previous works concerning the site-resolved position measurement [38][39][40][41][42] and continuous position measurement of a single quantum particle [43][44][45][46][47], the indistinguishability does not play such a nontrivial role. Our finding has the direct relevance to current techniques of in-situ observation of quantum gases [3][4][5][6][7][8][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 95%